Partisipasi Politik Masyarakat Tionghoa dalam Pemilihan Kepala Daerah di Slawi Kabupaten Tegal - Singestecia, Regina (Unnes Political Science Journal, 2018)
As a country that adopts democracy, Indonesian conducts general elections to choose their leaders. General elections of regional heads and deputy regional head held every five years. The political participation of the citizens is needed for the success of the democratic party. Just as the Chinese community, their participation is also needed because of their status as the citizens of Indonesia. This study was conducted to answer the question of how the political participation of the community and what are the factors affecting the Chinese community's political participation in the general elections of regional head and deputy regional head in 2014 at Slawi Wetan Village. This research was conducted in the Slawi Wetan Village, Tegal Regency. The method used in this research was descriptive qualitative. The data collection techniques used were interviews, observation and documentation. Meanwhile, the data analysis technique used in this study was the technique of interactive analysis which carried out in several steps of data collection, data reduction, data presentation, and conclusion. The results showed that there were 142 chinese people who were registered in the voters list in the general elections of regional head and deputy regional head 2014 in Slawi Wetan village. The level of political participation of the Chinese community in Slawi Wetan Village in the general election of regional head and deputy head of the region in 2014 occupied the Delegate Power. The Chinese community's political participation can be shown from the various forms of political participation that consists of informal political discussion and voting. In the implementation, there were factors that affect the Chinese community in the political participation.